142 Pediatric Epilepsy Outcomes After Laser Ablation: An Institutional Cohort Analysis. (April 2023) - Li, Daphne; Barros Guinle, Maria Isabel; Johnstone, Thomas; Kaur, Harsheen; Porter, Brenda; Grant, Gerald A.
Abstract : INTRODUCTION: Laser interstitial thermotherapy (LiTT) is a minimally invasive technique for targeting epileptogenic foci but there is limited data on outcomes in pediatric epilepsy. METHODS: A retrospective review of consecutive pediatric epilepsy patients at Stanford who underwent invasive stereoelectroencephalography between May 2017 to August 2021 and LiTT ablation of epileptogenic foci. Patient demographic, medication usage, seizure, prior surgical interventions, procedural details, and pre- and post-operative seizure history were analyzed. RESULTS: Thirty-five patients (24 male, 11 female) identified with average seizure onset 2.8 ± 2.8 years (range 0.25-12)) and average age 9.3 ± 5 years at the time of LiTT (range 2.4-17.9). Etiologies include 21 lesional patients (16 tuberous sclerosis, 4 focal cortical dysplasia, 1 gliosis), and 14 non-lesional (5 insular, 2 frontal, 5 temporal lobe, 2 had multiple foci). Eighteen patients had prior interventions including open resections n = 13 (singular n = 11, multiple n = 2), LiTT (n = 4) or a combination (n = 1), of which LiTT targeted a nearby area in 5. The median number of lasers placed in each procedure was 3 (range 1-5). Complications occurred in 13 cases (37%): 1 venous hemorrhage requiring evacuation intraoperatively, 1 aseptic meningitis, 2 immediate post-operative seizures, and 9 neurologic deficits (6 improving with therapy, 3 stable). Average post-operative length of stay is 2.11 ± 2.11 days (median 1, range: 1-9). Postoperatively, 18 patients (51.43%) were seizure free and median Engel score was 1 (Engel 1 n = 18, Engel 2 n = 6, Engel 3 n = 4, and Engel 4, n = 7) at last follow-up (average follow-up: 13.040 ± 11.37 months; range: 0.43-47.83). 15 (42.86%) patients were reported to experience neurocognitive or behavioral improvement, but this was not found to correlate with lower engel score (p = 0.777). CONCLUSIONS: LiTT is a safe and effective method of treatment for pediatric patients with medically refractory epilepsy of various etiologies.